Comparison of three exercise interventions with and without gemcitabine treatment on pancreatic tumor growth in mice: No impact on tumor infiltrating lymphocytes - Gupta, Priti; Hodgman, Charles F.; Alvarez-Florez, Claudia; Schadler, Keri L.; Markofski, Melissa M.; O’Connor, Daniel P.; LaVoy, Emily C. (Frontiers in Physiology, 2022)
Exercise has been shown to slow pancreatic tumor growth, but whether exercise interventions of differing volume or intensity yield differential effects on tumor outcomes is unknown. In this study, we compared three exercise training interventions implemented with and without chemotherapy on pancreatic tumor growth in mice. Methods: Male C57BL/6 mice (6-8 weeks old) were subcutaneously inoculated with pancreatic ductal adenocarcinoma tumor cells (PDAC 4662). Upon tumor detection, mice received gemcitabine 15 mg/kg intraperitoneally 3 days/week and were assigned to exercise: high volume continuous exercise (HVCE), low volume continuous exercise (LVCE), high intensity interval training (HIIT), or sedentary (SED). HVCE ran at 12m/min for 45 min and LVCE for 15 min, 5 days/week. HIIT ran one-min at 20m/min, followed by one-min walking at 8m/min for 20 total intervals, 3 days/week. SED did not run. Additional sets of inoculated mice were assigned to the exercise interventions but did not receive gemcitabine. Tumor volume was measured every other day for 2 weeks; tumor-infiltrating lymphocytes were assessed by flow cytometry 3-weeks post-inoculation. Results: Tumor growth did not differ between groups that received gemcitabine (F(3, 34) = 1.487; p = 0.235; η2 = 0.116). In contrast, tumor growth differed between groups not provided gemcitabine (F(3,14) = 3.364; p = 0.049, η2 = 0. 419), with trends for slower growth in LVCE than SED (p=0.088) and HIIT (p=0.084). Groups did not differ in tumor infiltrating lymphocytes. Conclusions: Contrary to our hypotheses, the exercise interventions compared here did not further reduce pancreatic tumor growth beyond that provided by gemcitabine. However, in mice not receiving gemcitabine, there was a trend for reduced tumor growth in LVCE.